Glass houses eaudiobook - Caine, Rachel (Morganville Vampires, 2009)
Morganville, Texas, is a small college town filled with quirky characters. But when the sun goes down, the bad come out. Because in Morganville, there is an evil that lurks in the darkest shadows—one that will spill out into the bright light of day. Claire Danvers has had enough of her nightmarish dorm situation. The popular girls never let her forget just where she ranks on the school's social scene: somewhere less than zero. And Claire really doesn't have the right connections—to the undead who run the town. When Claire heads off campus, the imposing old house where she finds a room may not be much better. Her new roommates don't show many signs of life. But they'll have Claire's back when the town's deepest secrets come crawling out, hungry for fresh blood.